ANALYSIS OF THE FAMILY HOPE PROGRAM (PKH) IMPLEMENTATION IN ADDRESSING SOCIAL WELFARE ISSUES IN MANADO CITY, NORTH SULAWESI PROVINCE - Inkiriwang, Imelda Emilia; Effendy, Khasan (Jurnal Tatapamong, 2024)
The Ministry of Social Affairs administers the Family Hope Program (PKH), a poverty alleviation and social protection initiative providing conditional non-cash assistance to individuals with social issues (PMKS), focusing on health, education, and social welfare. This research aims to evaluate the implementation of the Family Hope Program in Manado City, identify the challenges and obstacles encountered, and assess how the Manado City Social Service addresses these issues. The research employs a descriptive qualitative research method with an inductive approach. Data were collected through interviews, observations, and documentation, and analyzed using techniques including data collection, reduction, presentation, and conclusion drawing. The findings indicate that the implementation of the Family Hope Program in Manado City aligns with William Dunn's evaluation theory, meeting six key indicators: effectiveness, efficiency, adequacy, equity, responsiveness, and accuracy. The program's implementation is assessed as satisfactory across these indicators.